Scientometric cognitive and evaluation on smart city related construction and building journals data - Su, Liang-xing; Lyu, Peng-hui; Yang, Zheng; Ding, Shuai; Zhou, Kai-le (Scientometrics, 2015)
In this paper, scientometrics cognitive and knowledge visualization technology were used to evaluate global scientific production and development trends in construction and building technology research of smart cities. All the data was collected from the Science Citation Index-Expanded (SCIE) database and Journal Citation Reports (JCR). The published papers from the subject of construction and building technology and their journals, authors, countries and keywords spanning over several aspects of research topics, proved that architecture/building research grew rapidly over the past 30 years, and the trend still continues in recent smart cities era. The purposed of this study were to identify the journals in the field of construction and building technology in smart city, make a comparative report on related researches, as well as propose a quality evaluation of those journals. Based on JCR and SCI paper data, the journals related to construction and building technology in smart city were assessed using ten metrics: languages, active degree, references, citation trends, main countries, leading institutes, cooperation trends, productive authors, author keywords and keywords plus. The results indicate that all the factors have great significance and are related to the impact of a journal. It also provides guidance to both evaluators and the study groups which assess journals during the process of judging or selecting research outlets, and future perspective on how to improve the impact of a paper or a journal.